Teaching Reading Comprehension to Students with Learning Difficulties. - Vaughn. Sharon (The Guilford Press, 2024)
Now in a revised and expanded third edition, this important resource helps teachers understand how good readers comprehend text and how best to support students who are struggling. It presents effective instructional methods for learners at all grade levels, including those with reading disabilities. Every chapter translates state-of-the-art research into practical classroom applications. All facets of comprehension are addressed, including assessment, vocabulary, background knowledge, and text structure. Chapters also cover English learners, intensive intervention, and content literacy. Utility as a teacher guide and course text is enhanced by sample lesson plans, graphic organizers, and chapter-opening study questions.